girl boy bakla LESBIANA a discourse analysis of the lesbian representation on the television show Maalaala Mo Kaya ? - Queyquep, Maria Lucille Angeli Francisco 1990- (2012)
"This qualitative study aspired to analyze the lesbian representation in the television medium trough ABS-CBN's drama anthology, Maalaala Mo Kaya. The period covered analysis from the year 1998 to 2010. Hence, there were four episodes of the show that served as my study materials, namely: Boy Shoes (1998), Songbook (2002), Juice (2006) and Kwintas (2010). Using most of Judith Butler's assertion about Queer Theory as springboard and the concepts of Representation by cultural theorist Stuart Hall, I analyzed underlying discourses about lesbianism among my research materials. The results of the study turned out to be be inevitably predictable but at the same time surprisingly magnificent. It had been very apparent how certain stereotypes about lesbianism were found on the materials. However, I was also able to observe how the disposition of the lesbian characters that were represented have changed through time and developed to be remarkably notable to the very inspiration that led me to write this study which was lesbian struggle for visibility and empowerment."